A person-centred approach in medicine to reduce the psychosocial and existential burden of chronic and life-threatening medical illness. (3rd September 2017) - Grassi, Luigi; Mezzich, Juan E.; Nanni, Maria Giulia; Riba, Michelle B.; Sabato, Silvana; Caruso, Rosangela
Abstract: The psychiatric, psychosocial, and existential/spiritual pain determined by chronic medical disorders, especially if in advanced stages, have been repeatedly underlined. The right to approach patients as persons, rather than symptoms of organs to be repaired, has also been reported, from Paul Tournier to Karl Jaspers, in opposition and contrast with the technically-enhanced evidence-based domain of sciences that have reduced the patients to 'objects' and weakened the physician's identity deprived of its ethical value of meeting, listening, and treating subjects. The paper will discuss the main psychosocial and existential burden related to chronic and advanced medical illnesses, and the diagnostic and therapeutic implications for a dignity preserving care within a person-centred approach in medicine, examined in terms of care of the person (of the person's whole health), for the person (for the fulfilment of the person's health aspirations), by the person (with physicians extending themselves as total human beings), and with the person (working respectfully with the medically ill person).